A Computer-Based Approach to Solving the Diophantine Equation 7^x-3^y=100 - Dima, Andreea (The PUMP Journal of Undergraduate Research, 2022)
Assisted by Octave and by a website where one can find the order of a modulo m (here a and m are relatively prime natural numbers), I found a proof for showing that the diophantine equation 7^x - 3^y = 100 has only the solution (x,y) = (3,5) in positive integers.